Digital Preservation of Scientific Data - Barateiro, J. (2008)
Digital preservation aims at maintaining digital objects and data accessible over long periods of time. We propose the use of dedicated or surplus storage resources of data grids to build frameworks of digital preservation. In this paper we focus on the problem of digital preservation in two scenarios: a national digital library and a repository of scientific information for dam safety. We detail the scenario of dam safety data and provide an analysis of an existing data grid solution that can be used for this purpose.